PRP coating on different modified surfaces promoting the osteointegration of polyetheretherketone implant - Shi, Xiaotong; Wang, Zongliang; Guo, Min; Wang, Yu; Bi, Zhiguo; Li, Dongsong; Zhang, Peibiao; Liu, Jianguo (Frontiers in Bioengineering and Biotechnology, 2023)
Polyetheretherketone(PEEK) material implants have been applied more and more clinically recently. In order to increase the osteogenic activity of PEEK material, the microstructure change of the material surface and the construction of functional microcoatings have become a hot research topic. This study investigated the ability of PEEK surfaces modified by different methods to carry Platelet-rich plasma(PRP) and the osteogenic ability of different PEEK microstructures after carrying PRP in vivo/in vitro. In this study, PEEK Ssurfaces were modified by sulfuric acid, gaseous sulfur trioxide and sandpaper. Next, PRP from SD rats was prepared and incubated on PEEK material with different surface microstructures.The results of lactate dehydrogenase test, scanning electron microscope and Elisa assay showed that the sandpaper polished PEEK had the highest adhesion efficiency of PRP. The in vitro and in vivo tests further showed that the PRP coating on PEEK surface could significantly promote osteogenesis. And in this study, the sandpaper-polished PEEK with the strongest PRP carrying capacity showed the best osteogenesis. Our study found that the modified PEEK surface with PRP coating has excellent osteogenic ability and provided the basis for the interface selection of PRP for the further application of PEEK materials.